Strength of Capital Structure, Prudence and Audit Committee in Enhancing Profit Quality - Rendy Yunaldi; Erika Astriani Aprilia (GOVERNORS, 2022)
This study aims to determine the Effect of Capital Structure, Prudence and Audit Committee on Profit Quality. This study used a sample of manufacturing companies in the food and bavarages sub-sector listed on the Indonesia Stock Exchange during the period 2016 to 2020, the number of companies sampled in this study was 12 companies with observations for 5 years. Based on the purposive sampling method, the total sample of this study is 60 annual reports. The data collection method used is secondary data, which is data obtained by researchers indirectly through intermediary media and literature studies. The data in this study was obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id and several company websites. From the results of the t test analysis (partial) shows that the Capital Structure and Prudence have a significant influence on the quality of profits. Meanwhile, the Audit Committee does not have a significant influence on the quality of profits. So, audit committee will not be too important to organized